Seroprevalence of brucellosis, knowledge, and risky practices in dairy cattle owners and workers in Maekel and Debub regions, Eritrea - Efrem, G.H.; Mihreteab, B.; Ghebremariam, M.K.; Tesfai, B.; Mor, Siobhan M.; Mamo, G. (American Society of Tropical Medicine and Hygiene, 2024)
Brucellosis is a zoonotic disease with worldwide distribution. In Eritrea, the status of the disease in occupa tionally exposed dairy farmers is unknown. The objective of this study was to determine the seroprevalence of brucellosis, level of knowledge, and risky practices of dairy cattle owners/workers in Maekel and Debub regions, Eritrea. A cross sectional study was conducted between August 2021 and February 2022. A total of 416 dairy cattle owners and workers underwent blood collection and interview using a standardized questionnaire. Blood samples were tested using Rose Ben gal Plate Test, and positive samples were confirmed using competitive ELISA. Variation in knowledge scores by sociode mographic factors and practices were explored statistically. The apparent and true seroprevalence was 1.2% (95% CI: 0.05–2.8%) and 1.4% (95% CI: 0.6–3.4%), respectively. Apparent seroprevalence was similar in Maekel (1.1%) and Debub (1.2%) regions. Nearly half of the participants (49.5%) had never heard of brucellosis before. Overall, brucellosis knowledge score was low (mean score: 6.53/20). Knowledge score was higher in participants from Maekel region (P < 0.001), older participants (P = 0.035), those with higher educational attainment (P = 0.001), and those with more years of experience working in dairy farming (P = 0.001). Knowledge score was lower in farm workers compared with family members (P = 0.016). No significant differences in knowledge score existed between participants who engaged in or did not engage in potential risky practices. In summary, the prevalence of brucellosis in dairy cattle owners/workers in Maekel and Debub regions, Eritrea, was low. Participants demonstrated limited knowledge of brucellosis and engaged in risky practices.